2019
DOI: 10.2105/ajph.2019.305229
|View full text |Cite
|
Sign up to set email alerts
|

Price Promotions by Food Category and Product Healthiness in an Australian Supermarket Chain, 2017–2018

Abstract: Objectives. To examine the prevalence and magnitude of price promotions in a major Australian supermarket and how they differ between core (healthy) and discretionary (less healthy) food categories. Methods. Weekly online price data (regular retail price, discount price, and promotion type) on 1579 foods were collected for 1 year (April 2017 to April 2018) from the largest Australian supermarket chain. Products audited were classified according to Australian Dietary Guidelines definitions of core and discreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 26 publications
4
64
5
Order By: Relevance
“…No experimental studies were identified. Eight studies primarily examined the prevalence of price promotions (“prevalence studies”), and eight examined the influence of price promotions on purchasing behaviour (“influence studies”). All 16 studies were conducted in high‐income countries, with four in the United States, seven in the United Kingdom, one in the Republic of Ireland, two in Australia, one in New Zealand, and one in The Netherlands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No experimental studies were identified. Eight studies primarily examined the prevalence of price promotions (“prevalence studies”), and eight examined the influence of price promotions on purchasing behaviour (“influence studies”). All 16 studies were conducted in high‐income countries, with four in the United States, seven in the United Kingdom, one in the Republic of Ireland, two in Australia, one in New Zealand, and one in The Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies that examined prevalence of food and/or beverage price promotions (n = 8), most (n = 7) compared the prevalence of price promotions between healthy and unhealthy foods and beverages, with one study reporting on the prevalence of price promotions for unhealthy products only. All influence studies stratified at least part of their analysis by socio‐economic or sociodemographic subgroups, but only one study examined variance in the association between product healthiness and price promotions purchases by an indicator of SEP—household income level .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, an increasing density of supermarkets was observed and it is known that supermarkets sell unhealthy foods and beverages and encourage purchasing through strategic placement and price promotions of these products [38,[57][58][59]. Since Australians make two-thirds of food and beverage purchases (excluding alcohol) at supermarkets [60], further examination of the implications of in-store promotion and placement is needed.…”
Section: Implications For Practicementioning
confidence: 91%
“…These marketing techniques increase the likelihood that consumers will make impulse purchases (13). They are predominantly used for the promotion of unhealthy foods and drinks (14)(15)(16)(17), however, despite evidence that these strategies can also be used to promote healthy food choices in supermarkets (18)(19)(20). Checkout counters are an unavoidable point in supermarkets, and they are characterized by high levels of impulsive food purchases (21,22).…”
mentioning
confidence: 99%